2016
DOI: 10.1007/s13365-016-0444-5
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesviruses induce different cell death forms in neuronal and glial-derived tumor cell cultures

Abstract: Oncolytic viruses have the ability to infect tumor cells and leave healthy cells intact. In this study, bovine herpesvirus 1 (BHV1; Los Angeles, Cooper, and SV56/90 strains) and bovine herpesvirus 5 (BHV5; SV507/99 and GU9457818 strains) were used to infect two neuronal tumor cell lineages: neuro2a (mouse neuroblastoma cells) and C6 (rat glial cells). BHV1 and BHV5 strains infected both cell lines and positively correlated with viral antigen detection (p < 0.005). When neuro2a cells were infected by Los Angele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
(105 reference statements)
2
19
1
Order By: Relevance
“…These results are in accordance with the decrease of viability and the high viral titers in these cell lines, confirming the ability of the virus to induce apoptosis. This is consistent with our previous studies, which demonstrated that CpHV-1 during lytic cycle exert its replicative potential inducing apoptosis in ruminant epithelial cells, in peripheral blood mononuclear cells and in a murine neuroblastoma cell line 16,17 and agree with the results obtained by Cardoso et al, 15 who has demonstrated that oncolytic potential of BoHV-1 is mediated by apoptosis induction in glial-derived tumour cell cultures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in accordance with the decrease of viability and the high viral titers in these cell lines, confirming the ability of the virus to induce apoptosis. This is consistent with our previous studies, which demonstrated that CpHV-1 during lytic cycle exert its replicative potential inducing apoptosis in ruminant epithelial cells, in peripheral blood mononuclear cells and in a murine neuroblastoma cell line 16,17 and agree with the results obtained by Cardoso et al, 15 who has demonstrated that oncolytic potential of BoHV-1 is mediated by apoptosis induction in glial-derived tumour cell cultures.…”
Section: Discussionsupporting
confidence: 94%
“…In this context, Caprine Herpesvirus type 1 (CpHV-1) has been used, in the present study, to kill some neoplastic cell lines of different origin, assuming that CpHV-1 owns oncolytic capacities like other Alphaherpesvirus such as Bovine Herpesvirus Type 1 (BoHV-1) and Equine Herpesvirus Type 1 (EHV-1). [13][14][15] Our group has previously shown that CpHV-1 induces apoptosis in a permissive cell line (Madin Darby Bovine Kidney, MDBK 16 and in goat Peripheral Blood Mononuclear Cells (PBMCs), 17 and recently, we also have investigated about the apoptotic pathway activation during CpHV-1 infection by gene expression response analysis in a murine neuroblastoma cell line (Neuro 2A). 18 Thus, the aim of this study was to investigate the capacity of CpHV-1 to grow in and impair cellular viability of human normal and neoplastic cell lines (HEL-299, Vero, HeLa, U2OS, MDAMB-468, A549, PC3, K562).…”
Section: Introductionmentioning
confidence: 99%
“…HSV-1 infection elevates cellular ROS levlels in murine microglial cells, which is associated with production of proinflammatory cytokines and neural cell damage [ 15 , 16 ]. ROS overproduction and different cell death forms were induced in neuronal and glial-derived tumor cells following BoHV-1 and BoHV-5 infection [ 17 ]. These studies unanimously addressed the importance of ROS in herpesvirus induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis is an immune defense mechanism in which caspase-8 activity is inhibited and apoptosis cannot occur. Current studies have shown that human herpesviruses HSV-1 and HSV-2 can cause necroptosis of murine cells and human cells and that veterinary herpesviruses BHV-1 and BHV-5 can cause necroptosis of nerve cells [ 129 , 130 ]. HSV R1 protein (HSV-1 ICP6 and HSV-2 ICP10) plays an important role in the regulation of apoptosis and necroptosis.…”
Section: The Roles Of Apoptosis Autophagy and Necroptosis In Alpha-hmentioning
confidence: 99%
“…Furthermore, although some cross-reactivity between BHV-1 and HSV-1 exists, the majority of human antibody or serum samples tested failed to neutralize BHV-1 despite possessing HSV-1 neutralizing capacity [ 150 ]. Moreover, BHV-1 infection of neuronal- and glial-derived tumor cell cultures can induce ROS production, mitochondrial membrane dysfunction, apoptotic cell death and necroptotic cell death [ 129 ]. Another animal herpesvirus, EHV-1, productively infects human glioblastoma cell lines and significantly induces apoptosis, and the degree of infection is positively correlated with glioma cell death [ 151 ].…”
Section: The Roles Of Apoptosis Autophagy and Necroptosis In Alpha-hmentioning
confidence: 99%